Camu‐camu (Myrciaria dubia) from commercial cultivation has higher levels of bioactive compounds than native cultivation (Amazon Forest) and presents antimutagenic effects in vivo. (2nd August 2018) - Azevedo, Luciana; de Araujo Ribeiro, Paula F; de Carvalho Oliveira, Jéssica A; Correia, Maryana G; Ramos, Flávia M; de Oliveira, Eduardo B; Barros, Frederico; Stringheta, Paulo C
Abstract: BACKGROUND: Camu‐camu ( Myrciaria dubia ) is a typical Amazonian fruit and has high antioxidant capacity due to its high levels of vitamin C and phenolic compounds. This study aimed to determine the phytochemicals, antioxidant capacity and antimutagenic effects of camu‐camu fruits with different maturity stages grown in dry (commercial cultivation) or flooded environments (native cultivation, Amazon). RESULTS: Total polyphenols, ascorbic acid and in vitro antioxidant capacity levels were higher in ripe fruits grown in a commercial cultivation. The extracts from ripe camu‐camu grown in a commercial cultivation exerted antioxidant effects and high percentage of protection against doxorubicin and 1, 2‐dimethylhydrazine in all tested systems (liver, bone marrow and gut), for three camu‐camu extract concentrations (17, 85 and 170 mg kg −1 body weight), as follows: bone marrow minocronucleus (37.91%, 41.75%, 43.95%); micronucleus gut test (61.01%, 64.40%, 50.28%); apoptosis index (60.26%, 62.44%, 58.22%); comet assay through the tail moment (71.64%, 72.31%, 70.70%), percent DNA in the tail (64.54%, 68.75%, 76.79%) and tail intensity (76.43%, 81.02%, 68.33%). CONCLUSION: The results of this study contribute to increasing the production of camu‐camu fruits grown in dry environments and their use as a health‐promoting food. © 2018 Society of Chemical Industry